L-indistinguishability of eigenvarieties - Ludwig, Judith (Journal of the Institute of Mathematics of Jussieu, 2018)
In this article, we construct examples of L-indistinguishable overconvergent eigenforms for an inner form of SL2.
First published online 22 March 2016
Gesehen am 01.06.2021